Micro and nano plastics in groundwater systems: A review of current knowledge and future perspectives - Gundogdu, Sedat; Mihai, Florin-Constantin; Fischer, Elke Kerstin; Blettler, Martin C. M.; Turgay, Oguz Can; Akca, Muhittin Onur; Aydogan, Burak; Ayat, Berna (ELSEVIER SCI LTD, 2023)
Groundwater is a critical resource for drinking, agriculture, and domestic purposes but is under threat from micro and nano plastic (MNP) pollution. MNPs can contaminate aquifers through various sources such as industrial abrasives, personal care products, wastewater, and improper waste management. MNPs can enter groundwater through leaching or penetration and pose a risk to drinking water sources. Agriculture, municipal waste disposal, tire abrasion, and littering are major sources of MNP pollution in the soil. Despite increasing concern, knowledge about the occurrence and impacts of MNP in groundwater is still limited. Further research is necessary to understand the impact and mitigation strategies of MNP contamination. This review discusses the level of contamination, fate of MNPs in aquifers, transportation mechanisms, and potential impacts on human health. The study highlights the importance of implementing sustainable waste management practices to reduce MNP contamination in groundwater. & COPY; 2023 Elsevier B.V. All rights reserved.
Keywords: Microplastics; Nanoplastics; Groundwater pollution; Aquifer; Soil pollution; POROUS-MEDIA; TRANSPORT; WATER; RETENTION; COLLOIDS; SOILS; SHAPE; Chemistry